Extra-Gastric Manifestations of Helicobacter Infection Stages of Diagnosis and Treatment - Khudayberganova N.H; Rakhmatullayeva G.K; Azimova M.M; Tagayeva M.H.; Tagayeva M.H. (Peerian Journals Publishing, 2023)
The article presents the results of a survey of 105 children with pathology of the gastroduodenal zone, which was mainly combined with pathology of the biliary tract. The characteristic features of the anamnesis of these patients are given, the analysis of the diagnostic value of various symptoms detected by palpation of the anterior abdominal wall is carried out. The issues of verification of Helicobacter pylori infection using the Helik respiratory test, bacteriological and molecular genetic methods for analyzing biopsy specimens of the duodenal mucosa and duodenal contents are considered. It has been proven that Helicobacter pylori is less common in children with isolated forms of chronic gastroduodenitis (CGD) and biliary tract dysfunction (BDBD), compared with children with an organic lesion of the biliary system in the form of chronic cholecystocholangitis, which requires verification. Helicobacter pylori in the primary diagnosis of infection and subsequent etiotropic therapy
Keywords: chronic gastroduodenitis; combined pathology of the biliary tract; palpation of the anterior abdominal wall